Clinically and radiologically successful treatment of spondylitis by guselkumab in a patient with pustulotic arthro‐osteitis - Natsumi Ikumi; Hideki Fujita (Journal of Cutaneous Immunology and Allergy, 2023)
This article reported the first case of spondylitis due to pustulotic arthro‐osteitis that was successfully treated with anti‐IL‐23p19 antibody guselkumab in terms of improvement in imaging assessment in addition to that of clinical symptoms.